Solution of Second Kind Volterra Integral Equations Using Non-Polynomial Spline Functions (Baghdad Science Journal, 2025)
In this paper we use non-polynomial spline functions to develop numerical methods to approximate the solution of 2nd kind Volterra integral equations. Numerical examples are presented to illustrate the applications of these method, and to compare the computed results with other known methods.